2014
DOI: 10.1259/bjr.20140185
|View full text |Cite
|
Sign up to set email alerts
|

Non-osseous incidental findings in low-dose whole-body CT in patients with multiple myeloma

Abstract: Objective: The purpose of this study was to identify the frequency and grading of non-osseous incidental findings (NOIF) in non-contrast whole-body low-dose CT (LDCT) in patients with multiple myeloma. Methods: In the time period from 2010 to 2013, 93 patients with multiple myeloma were staged by non-contrast wholebody LDCT at our radiological department. LDCT images were analysed retrospectively for NOIF, which also included unsuspected extramedullary manifestation of multiple myeloma. All NOIF were classifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 19 publications
0
22
0
5
Order By: Relevance
“…3 Furthermore, the number of incidental findings varied from 2.8 to 3.2 per patient investigated. 3,9 Most frequently, different malignant lesions and cardiovascular findings incidentally detected on CT have been reported. 2,5,6,[8][9][10] Although skeletal muscles represent approximately 50% of total body mass, IFs on imaging investigations have been not reported previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Furthermore, the number of incidental findings varied from 2.8 to 3.2 per patient investigated. 3,9 Most frequently, different malignant lesions and cardiovascular findings incidentally detected on CT have been reported. 2,5,6,[8][9][10] Although skeletal muscles represent approximately 50% of total body mass, IFs on imaging investigations have been not reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…7 Most studies that analyzed incidental findings on imaging, especially on CT, focused on the prevalence of several incidentally detected malignancies or clinically relevant findings. [2][3][4][5][6][8][9][10] To the best of our knowledge, there were no previous reports regarding incidental findings in the skeletal musculature. However, it is the largest region of the body and may contain different findings.…”
Section: Introductionmentioning
confidence: 93%
“…Whole body low‐dose CT is capable of demonstrating extramedullary disease (Surov et al , ) and correlates with whole‐body MRI findings (Wolf et al , ). As well as extramedullary myeloma, WBLDCT demonstrates clinically significant non‐osseous incidental findings (NOIF), such as occult carcinoma and infection, so careful extra skeletal review is mandated.…”
Section: Use Of Imaging For Diagnosismentioning
confidence: 99%
“…As well as extramedullary myeloma, WBLDCT demonstrates clinically significant non‐osseous incidental findings (NOIF), such as occult carcinoma and infection, so careful extra skeletal review is mandated. Surov et al () retrospectively reported an average of 3·2 NOIF per patient which were clinically significant in 36·6% of 93 patients with myeloma undergoing WBLDCT.…”
Section: Use Of Imaging For Diagnosismentioning
confidence: 99%
“…In addition to the high sensitivity, CT has additional advantages such as improved assessment of fracture risk, the ability to visualize extraosseous myeloma, and biopsy, surgery, and radiation planning. Moreover, clinically relevant, non-bone-related secondary diagnoses can be made on CT in approximately one-third of cases (▶ Table 2) [17].…”
Section: Whole-body Ctmentioning
confidence: 99%